The Impacts of Traditional Fermentation Method on the Chemical Characteristics of Arabica Coffee Beans from Bondowoso District, East Java - Ika Oktavianawati; Sattya Arimurti; Suharjono Suharjono (Chemistry Department, The University of Brawijaya, 2020)
Bondowoso district is the predominant supplier of coffee beans, and also known as Republik Kopi. However, there was still insufficient data about the chemical characteristics of coffee from Bondowoso. This research has main aims to characterize the chemical characteristic of Coffea Arabica L. from Bondowoso, and determine the impact of traditional fermentation on them. Coffee beans were naturally-fermented through soaking in water for less than 12 hours. Unfermented coffee beans were used as a control. Both unfermented and fermented coffee beans were subjected to chemical analysis. Results show that total nitrogen and lipid contents of both fermented and unfermented beans decreased after fermentation into 0.19%±0.03 and 10.03%±0.14, respectively. LCMS analysis of coffee beans revealed that the majority of amino acid contents in fermented beans were higher than that found in unfermented beans, while caffeine and derivatives to be lower in fermented coffee beans than in unfermented beans. One exception for this was 7-methylxanthine, which was found only in fermented beans. Other metabolites, including procyanidines A and B, were found to decrease through fermentation. Interestingly, 3-flavanol was found only in fermented coffee beans. This research results would benefit on improving the quality of coffee through fermentation step.